Investigating the Prevalence, Severity, and Nature of Adverse Events in an Inpatient Rehabilitation Hospital - Shoeleh Rahimi; Hamid Reza Khankeh; Narges Arsalani; Masoud Fallahi-Khoshknab; Abbas Ebadi; Fereydoun Layeghi (Iranian Rehabilitation Journal, 2023)
Objectives: This study aims to evaluate the prevalence, severity, and nature of adverse events (AEs) and provide suggestions on how to prevent AEs recurrence in an inpatient rehabilitation hospital in Iran. Methods: This retrospective descriptive-analytical study was conducted in 2021 at Rofaydeh Rehabilitation Hospital in Tehran City, Iran. AEs associated with rehabilitation services and nursing care, which were reported in the hospital’s voluntary reporting system from 2018 to 2021 were evaluated. A standard checklist codified by the Ministry of Health of Iran was used to collect the data from the medical error documentation. The data were analyzed by the SPSS software, version 21, using descriptive statistics, the chi-square, and the Fisher exact tests. Results: A total of 5642 patients had been hospitalized in the study setting and 517 AEs had been documented during the 4 years of the study. The most common AEs in descending order were as follows: falls 288(55.7%), pressure ulcers 57(11.02%), medication errors 50(9.67%), clinical process 49(9.47%), clinical administration (issues with admission process 10(1.93%) and wrong patient identification 5(0.96%). Among 58(11.21%) cases of hospital-acquired infections, 45(77.58%) cases were urinary tract infections. There was a significant relationship between age and fall (P=0.026), pressure ulcer (P=0.006), and hospital-acquired infection (P=0.001), and between gender and fall (P=0.01), pressure ulcer (P=003), and hospital-acquired infection (P=0.01). The severity of identified AEs was categorized into mild 431(83.36%), moderate 61(11.79%), and severe 25(4.83%). The most common causes of AEs were limited supervision of patients by healthcare providers. Discussion: This study showed that patient fall, pressure ulcer, and hospital-acquired infection were the most prevalent AEs in the rehabilitation hospital. Future efforts to improve patient safety in these settings should focus on reducing such AEs along with removing barriers to voluntary incident reporting.